Can the common agricultural policy be reformed? - Ulrich Koester; Stefan Tangermann (Intereconomics, 1976)
Much criticism notwithstanding, the essentials of the common agricultural policy have up to now scarcely been changed. What kind of basic changes would have to be introduced for a new agricultural policy to become also politically acceptable? The following article suggests alternatives to the present agricultural policy — suggestions which the authors first made in a report prepared for the Federal Ministry of Food, Agriculture and Forests.
Keywords: 330; EC